Ambidextrous leadership of publicly listed companies during turbulent times: The importance of agility and alliance capability - Firdaus Alamsjah (Global Business & Finance Review (GBFR), 2022)
Purpose: The primary goal of this study is to evaluate the importance of developing organizational agility and alliance capability to survive during turbulence times such COVID-19 pandemic. Design/methodology/approach: The study's data was gathered through a survey of 103 top management teams from 55 publicly listed companies in Indonesia, and the responses were analyzed to determine the relationships between leadership, agile organization, alliance management, and firm performance. Findings: This study found that ambidextrous leadership at publicly listed companies has no direct impact on firm performance during times of turbulence. Agility and alliance management capability, on the other hand, fully mediate the relationship between ambidextrous leadership and firm performance. Research limitations/implications: Leaders, particularly those in public listed companies, must continuously improve their organizational agility and alliance management capability to remain competitive and adaptive to face environmental changes. For utilizing organizational agility and alliance management capability as a firm strategy during times of turbulences, ambidextrous leaders are expected to balance exploiting and exploring practices. Originality/value: This study compares the perceptions of top management team during and normal time and during the COVID-19 pandemic specifically on leadership, agility, and alliance management capability in a stock market environment.
Keywords: 650; Ambidextrous leadership; Organizational agility; Alliance management capability; Firm performance; Public listed company